Image quality and dose exposure of contrast-enhanced abdominal CT on a 1st generation clinical dual-source photon-counting detector CT in obese patients vs. a 2nd generation dual-source dual energy integrating detector CT. Issue 151 (June 2022) - Hagen, Florian; Hofmann, Johannes; Wrazidlo, Robin; Gutjahr, Ralf; Schmidt, Bernhard; Faby, Sebastian; Nikolaou, Konstantin; Horger, Marius
Highlights: PCD-CT allows a significant dose reduction (25%) with comparable image noise. With increasing BMI (Body Mass Index) the Δ CNR between PCD-CT and DSCT increases. Especially the CNRvessels was significantly higher in PCD-CT compared to the equivalent DSCT. Abstract: Purpose: To compare the radiation dose as well as the image quality of contrast-enhanced abdominal 1st-generation Photon-Counting Detector CT (PCD-CT) to a 2nd-generation Dual-Source Dual-Energy-Integrating-Detector CT (DSCT) in obese patients. Method: 51 overweight (BMI ≥ 25 kg m 2 ) patients (median age: 67.00 years; IQR: 59.00–73.00, median BMI 32.15 kg m 2 ; IQR: 28.70–35.76) who underwent clinically indicated, contrast-enhanced abdominal-CT in portal-venous phase on both 2nd-generation DSCT and on a commercially available 1st-generation PCD-CT were prospectively included the degree of obesity was defined by BMI-calculation (overweight, obesity grade I/30–34.9; obesity grade II/35–39.9; obesity grade III > 40) and by the absolute weight value. The same contrast media and pump protocol were used for both scans. PCD-CT was performed in Quantumplus mode at 120 kVp whereas DSCT used also 120 kVp in single energy mode. Comparable convolution algorithm between DSCT and PCD-CT were set. For both scanners, polychromatic images were reconstructed; for PCD-CT data from all counted events above the lowest energy threshold at 20 keV (termed T3D) were used. Two independent radiologists assessed subjective image quality using a 5-point Likert-scale and quantified the contrast-to-noise ratio of parenchymatous organs and vascular structures. Results: Median time interval between the scans was 4 months (IQR 3–7 months). BMI was classified overweight (n = 18, 35.3%), grade I (n = 19, 37.3%), II (n = 9, 17.6%), III (n = 5, 9.8%). Mean CNRrenal_cortex (12.35 ± 3.77 vs. 14.16 ± 3.55) as well as median CNRvessels (9.88 vs. 12.40) and median CNRpancreas (2.81 vs. 4.04) of PCD-CT were significantly higher than those at DSCT (p < 0.05). The inter-reader agreement for all subjective image quality readings was moderate to substantial. Both radiologists independently rated the image quality higher for PCD-CT data sets (p < 0.05). Median CTDI and DLP values for PCD-CT and DSCT were 12.00 mGy (IQR: 10.20–13.50 mGy) vs. 16.05 mGy (IQR: 14.81–17.98) and 608 mGy * cm (IQR: 521.00–748.00 mGy * cm) vs. and 821.90 mGy * cm (IQR: 709.30–954.00 mGy * cm) (p < 0.001). Conclusion: Significant dose reduction by similar or even improved image quality was obtained with abdominal contrast-enhanced CT using PCD-CT in obese patients as compared to 2nd-generation DSCT.